Long‐term outcome of periprosthetic joint infection following unicompartmental knee arthroplasty: A single‐centre case series - Kevin‐Arno Koch; Johannes Weishorn; Jakob Freytag; Pia‐Elena Frey; Mustafa Hariri; Christian Merle; Tilman Walker (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose Periprosthetic joint infection (PJI) following unicompartmental knee arthroplasty (UKA) is a rare but serious complication. The data available on this topic are heterogeneous and limited, particularly in regard to long‐term survival and patient‐reported outcomes (PROs). Therefore, the aim of the present study was to analyse the long‐term survival and functional outcome of a case series of PJI following primary UKA at a tertiary referral centre. Methods Eighteen knees treated for acute or chronic PJI after primary UKA between 2001 and 2020 with a minimum follow‐up of 2 years were retrospectively identified and evaluated in the present study. Surgical treatment included debridement, antibiotics and implant retention (DAIR) in 10 patients, and two‐stage arthroplasty in 8 patients. Implant survival analysis was conducted using the Kaplan–Meier estimator. Patient‐reported outcome measures (PROMs) were used to assess clinical outcomes. Results Overall implant survival free from any revision at 10 years was 83% (95% confidence interval [CI]: 57%–94%). Three DAIR procedures failed due to persistent infection with partially major complications, resulting in a 10‐year revision‐free implant survival of 73% (95% CI: 37%–90%). No reoperation was required in the group that underwent staged treatment. There were no long‐term revisions due to aseptic loosening or degeneration of other compartments in either group. Both groups demonstrated promising median Oxford Knee Scores, with no significant difference (>0.05) between the DAIR (42, range 11–45) and two‐stage exchange arthroplasty (43, range 19–46) groups. Conclusions Two‐stage revision procedure offers excellent long‐term survival and high patient satisfaction. The DAIR procedure represents a valid treatment option for acute PJI but carries a certain risk of treatment failure that surgeons should be aware of. Successful treatment of PJI in UKA can provide excellent functional outcomes and long‐term survival without an increased risk of low‐grade infection and aseptic loosening. Level of Evidence Level IV.